Organ Cultures for Retinal Diseases - Hurst, José; Fietz, Agnes; Tsai, Teresa; Joachim, Stephanie C.; Schnichels, Sven (Frontiers in Neuroscience, 2020)
Successful development of novel therapies is closely linked with understanding the underlying pathophysiology of a disease. Hence, model systems are needed that faithfully reflect human diseases and allow the evaluation of new therapeutic approaches. Preclinical animal studies have had limited success in predicting human physiology, pathology, and therapeutic responses. Besides this fact animals testing is facing more and more ethical and bureaucratic hurdles. On the other hand, human cell cultures are also limited in their ability to represent in vivo situations due to the lack of the microenvironment, which may alter cellular responses. To overcome these struggles, organ cultures, especially of complex organs such as the retina, can be used to study physiological reactions to substances or stressors. Human and animal organ cultures are now well established and recognised. This mini-review discusses how retinal organ cultures can be used to preserve the tissue architecture more realistically and therefore represent better disease-related changes. It also shows how molecular biological, biochemical and histological techniques can be combined to investigate how anatomical localization can alter cellular responses. Examples for the use of retinal organ cultures (including models to study AMD, RP, CRAO and glaucoma) are presented and their advantages and disadvantages are discussed. In conclusion, organ cultures allow significant progress in our understanding of complex retinal diseases and may furthermore advance the treatment testing without the need of animal testing.